ANALISIS PERSEPSI MAHASISWA TERHADAP RELEVANSI AMANAT AGUNG PADA KONTEKS GENERASI Z - Saran Parade M Lumbantoruan; Junita G. L. P. Aruan; Nurasyah Dewi Napitupulu (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
The Great Commission (Matthew 28:19-20) faces significant challenges in the context of Generation Z. This study aims to examine the perceptions of Christian students regarding the relevance of the Great Commission in the Generation Z environment. A survey was conducted among 101 Christian students aged 18-24. The data was collected using a questionnaire with three indicators of the perception of the Great Commission's relevance: understanding, application, and influence. Each indicator consists of 10 questions with four options in the form of a Likert scale. The results indicate that there is a stronger understanding of the Great Commission than its application and influence in Gen Z's life. The study's findings indicate that while there is a robust theological grasp of the Great Commission, the primary challenge lies in its practical implementation to enhance its influence on Gen Z. To address this challenge, churches and educational institutions must adapt to the digital lifestyle of Gen Z.